THE MOVEMENTS OF BUJANG GANONG DANCE OF REOG PONOROGO, EAST JAVA - Wahyu Yuga Utama; Nunuk Tri Hapsari (Sekolah Tinggi Bahasa Asing LIA Yogyakarta, 2021)
Bujang Ganong is a traditional dance of Ponorogo. This traditional dance is a part of Reog dance performance. In general, it portrays a story of a prime minister of a kingdom who is agile, clever, and humorous yet really powerful. The movements of Bujang Ganong dance are nimble, funny, and acrobatic. This study discusses the movements of Bujang Ganong after being homogenized in 1992, and finds out the differences between Bujang Ganong dance with National Reog Festival style and Obyok style. The writer did library research and interview’s data. The results show that after the homogenization in 1992, there are nine basic movements of Bujang Ganong dance which are still used and performed these days. Furthermore, the performance of Bujang Ganong with National Reog Festival style depicts the character of Bujang Ganong in the Bantarangin version, and the dancers barely have a chance to improvise the choreography. Meanwhile, Bujang Ganong with Obyok style is depicted more as such an entertainment with a great sense of humor.